Telaah kritis terhadap Undang-Undang No. 32 Tahun 2004 tentang Pemerintahan Daerah - Suharno Suharno (Universitas Negeri Yogyakarta, 2004)
The Constitution (UUD 1945) actually gave an opportunity for implementation of decentralist governmental system. But the New Order's Regime was not given enough manual for institutionalized decentralist government system. The idea to implement decentralist government system keep roll on until the issue of the Bill on Local Government No.32 Tabun 2004 as a completion of its previous. The wide authority to implement local governmental autonomy given by that bill implied politically as the discretion, scope and volume of local politic being wider and by managerial also make the tasks and responsibility of local government being wider and heavier.